Os benefícios do incentivo à leitura na terceira idade - SOUSA, Juliana Andreza de (2019)
Shows the contribution of the librarian to promote reading in the third age. Discusses the importance of reading in the third age for the development of self-esteem and social integration. The Bibliotherapy as therapeutic process drawn from a program of selected activities, involving the reading materials specifically developed for emotional problems, among others. The methodological path is from an exploratory research with qualitative approach and a bibliography. The results exposed, imply, the world of reading this in the daily lives of the elderly, actions that can be developed from the arguments of authors and their connections about the world the practice of reading in the best age, that is, in the elderly. In the end, the thoughtful way reveals that as information professionals, librarians, based on the oath of humanistic nature and the dignity of the human person, social contribution, you look at the social groups in need of reading in their every day, once in the reading understandable forms of legitimacy for human dignity, but that however lack development actions and policies that will contribute to the strengthening of reading in the third age. In this way, is a reflection of our professional contribution in society in mediate where there are readers in need of information